Deep Vein Thrombosis is Modulated by Inflammation Regulated via Sirtuin 1/NF-κB Signalling Pathway in a Rat Model - Yao, Xiaolan; Chen, Wenpei; Liu, Jin; Liu, Han; Zhan, Janis Y.; Guan, Shixia; Lu, Ziqi; Tang, Ping; Li, Peng; Lin, Baoqin (Thrombosis and Haemostasis, 2019)
Background Inflammation plays an important role in thrombus formation, and Sirtuin 1 (SIRT1) negatively regulates inflammation via deacetylating nuclear factor-kappa B. However, the relationship between SIRT1-regulated inflammation and deep vein thrombosis (DVT) is still unknown.Objective The aim of this study was to investigate whether SIRT1 plays a critical role in inferior vena cava (IVC) stenosis-induced DVT.Materials and Methods Thrombus weight and histopathologic analysis of IVC were evaluated at different time points after IVC stenosis in rats. Serum levels of inflammatory cytokines and protein expressions of SIRT1, acetylated p65 (Ace-p65), phosphorylated p65 (p-p65) and tissue factor (TF) in thrombosed IVC were assessed. Besides, the effects of resveratrol (RES, a SIRT1 agonist) and EX527 (a selective SIRT1 inhibitor) on DVT were evaluated.Results Thrombus weight was increased from 1 to 3 days after IVC stenosis, and then was decreased afterwards. Leukocytes infiltration appeared and serum levels of cytokines were significantly increased in rats of IVC stenosis. SIRT1 protein expression was significantly down-regulated at 1 hour and 1 day after stenosis, while p-p65, Ace-p65 and TF protein expressions appeared a contrary trend. RES reduced thrombus weight, leukocytes infiltration, levels of tumour necrosis factor-α and interleukin-1β and protein expressions of Ace-p65 and TF as well. Moreover, RES significantly increased the protein and messenger ribonucleic acid expressions of SIRT1, while EX527 abolished the protective effects of RES.Conclusion SIRT1 activation attenuated IVC stenosis-induced DVT via anti-inflammation in rats. Therefore, SIRT1 may be a potential therapeutic target that could ameliorate DVT.
Keywords: deep vein thrombosis; SIRT1; inflammation; resveratrol; EX527